The risk of amyotrophic lateral sclerosis after cancer in U.S. elderly adults: A population‐based prospective study. Issue 7 (28th February 2014) - Freedman, D. Michal; Wu, Jincao; Daugherty, Sarah E.; Kuncl, Ralph W.; Enewold, Lindsey R.; Pfeiffer, Ruth M.
Abstract : Although epidemiologic studies have examined the risk of amyotrophic lateral sclerosis (ALS) in relation to cancer, none have been large population‐based studies using incident ALS and adjusting for medical surveillance. Addressing those limitations, all first primary cancer cases from the Surveillance, Epidemiology and End Results (SEER) Program (1992–2005), linked to Medicare claims data were used. Cases were followed from cancer diagnosis until the earliest date of ALS diagnosis, a break in Medicare claims data, death, age 85 or December 31, 2005. A comparison group from a 5% random Medicare sample in the SEER areas who were cancer‐free and censored as above, or until a cancer diagnosis were selected. ALS outcomes were derived from medical claims. The proportional hazards models to estimate ALS hazard ratios (HRs), using age as the time scale, adjusting for sex, race and physician visits, and stratifying the baseline hazard on birth year and SEER registry were used. A total of 303 ALS cases were ascertained in cancer patients (2, 154, 062 person‐years) compared with 246 ALS cases (2, 467, 634 person‐years) in the reference population. There was no overall relationship between cancer and ALS (HR = 0.99; 95% CI = 0.81–1.22), nor by gender or race. Except for an elevated ALS risk in the first year after a leukemia diagnosis, the relationship between site‐specific cancers and ALS was null after correcting for multiple comparisons. Having a cancer diagnosis was not associated with an overall risk of incident ALS. The short‐term ALS risk after leukemia may reflect screening or reporting errors. Abstract : What's new? Studies suggest that incident Parkinson's disease and Alzheimer's disease are inversely associated with cancer, but whether the same is true for amyotrophic lateral sclerosis (ALS), another neurodegenerative disease, remains unclear. Here, following examination of incident ALS risk after cancer in a large population‐based study that controlled for medical surveillance, no overall association was found to exist between cancer and ALS risk. Heightened screening or reporting errors may be responsible for the detection of elevated ALS risk in the first year following leukemia diagnosis.